DEVELOPMENT OF A SET OF CONTROL EXERCISES BASED ON THE ASSESSMENT OF COMBAT CAPABILITIES - Blaus, Oskars; Bula-Biteniece, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
As the military environment is characterized by high levels of physical activity, physical activity is an important component of military action. The aim of the present study was to identify the most physically demanding daily and training (expected battle) tasks performed in the Latvian Army Land Force units (NAF LFU) through the development and application of a questionnaire survey. The results obtained in the study were used to start developing a set of NAF physical fitness control exercises. Based on adapted questionnaires, was developed a questionnaire for the NAF LFU, which allowed to determine most physically demanding daily and combat tasks, as well as dominant physical qualities and physical activities. The questionnaire was then distributed to 70 ground combat soldiers (with the most service and deployments experience as well as sports education), of whom 57 responded (81%). A field test – GB Combat test was carried out as part of the case study in the NAF LFU. Test was chosen by specialists and determined as the most suitable, evaluating the results of the questionnaire and the tasks to be performed by the NAF LFU. 52 soldiers participated in the pilot test. The five most physically demanding training tasks were identified: attack/ quick attack, fight in built-up area (FIBUA), defense, retreat/ delay and preparing fighting positions. The most common physical activities that characterize these tasks are indicated: crawling, running and bending, squatting. As the most important physical qualities indicated – muscular endurance 27.74%, less important physical qualities – speed 22.10%, muscular strength 21.32% and agility 20.36%. The five most physically demanding daily tasks were identified: field training, maintenance of equipment, marching, relocation of equipment and physical fitness training. The most common physical activities that characterize these tasks are indicated: carrying, lifting and running. As the most important physical qualities indicated - muscular endurance 33.08% and muscular strength 31.54%. The GB Combat test, evaluating by a rating system developed by the British Armed Forces (system - pass/fail), was not passed by 11 soldiers.